About the Approach to the Layering of Legal Regulation Through Municipal Services Provision in the Russian Federation - Androniak I. A. (Interactive science, 2021)
the article proposes an author's approach to the systematization of legal acts governing the provision of municipal services. At the same time, using the approach of A.Yu. Shumilov to the allocation of levels of legal regulation, the author systematized legal acts governing the provision of municipal services according to the following structure: constitutional level (basic) – middle level – detailing level – local level.
Keywords: правовое регулирование; государственная услуга; услуга; местное самоуправление; legal regulation; service; local self-government; муниципальные органы; уровни правового регулирования; municipal bodies; state service; levels of legal regulation